Book review: Harry R. Moody and Jennifer R. Sasser (2012). Aging: Concepts and Controversies (7th edition). Los Angeles, London, New Delhi, Singapore & Washington, DC: Sage Publications, 576 pp. ISBN 978 1 4522 0309 6 (paperback) - Andrzej Klimczuk (International Journal of Ageing and Later Life, 2015)
– This book is an unconventional introduction to basic gerontological issues. It is authored by Harry R. Moody and Jennifer R. Sasser, who are developing a theory of critical gerontology. Moody is well known for, among other things, his work with older adult education. He also recently retired as Vice President and Director of Academic Affairs for AARP in Washington, DC. In the seventh edition of Aging: Concepts and Controversies, he extended opportunity to work on the book as a co-author to Sasser, who works as a Chair and Associate Professor in the Department of Human Sciences at Marylhurst University in Portland, Oregon.
Keywords: J14; 330; Ageing